The way things work. Light [videorecording (DVD)] - Zamora, Diego; Macaulay, David (Schlessinger Media, 2003)
Two young Mammoth Islanders and a visiting inventor learn the properties of light by observing a room full of crystal trophies. They learn that light waves can do three things when they strike an object: they can bounce, they can pass through; or they can be absorbed. The Islanders also studied lenses to bend light, and they looked through telescopes, periscopes, and binoculars.